Scandal and silence media responses to presidential misconduct - Entman, Robert M. (Polity Press, 2012)
The author argues that "media neglect most corruption, providing too little, not too much scandal coverage; scandals arise from rational, controlled processes, not emotional frenzies -- and when scandals happen, it's not the media but government and political parties that drive the process and any excesses that might occur; significant scandals are difficult for news organizations to initiate and harder for them to maintain and bring to appropriate closure; for these reasons cover-ups and lying often work, and truth remains essentially unrecorded, unremembered."--Back cover